2019
DOI: 10.3892/mmr.2019.10631
|View full text |Cite
|
Sign up to set email alerts
|

Expression and function of Toll‑like receptors in peripheral blood mononuclear cells in patients with ankylosing spondylitis

Abstract: Ankylosing spondylitis (AS) is a common chronic inflammatory autoimmune disease. Toll-like receptors (TLRs) are involved in non-specific immunity. In the present study, the roles of TLRs in AS were investigated. The levels of inflammatory cytokines were detected by ELISA and reverse transcription-quantitative polymerase chain reaction (RT-qPCR). The expression levels of TLRs and nuclear factor-κB (NF-κB) signaling-associated factors were determined via RT-qPCR and western blot analyses. It was observed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 53 publications
1
24
0
Order By: Relevance
“…Previous studies found that Th1 and Th2 chemoattractants played a cooperative role in the development of AS. Th1 and Th2 chemokine levels decreased under etanercept, a TNF-a blocker, to improve the activity and functional capacity of AS patients (Ergin et al, 2011;Wang et al, 2016;Zhang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that Th1 and Th2 chemoattractants played a cooperative role in the development of AS. Th1 and Th2 chemokine levels decreased under etanercept, a TNF-a blocker, to improve the activity and functional capacity of AS patients (Ergin et al, 2011;Wang et al, 2016;Zhang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…And after treatment with anti-TNF drugs, the gene expression of TLR4 significantly decreased (Assassi et al, 2011). Similarly, another study also reported that TLR4 mRNA significantly increased in AS patients (Zhang et al, 2019). All the aforementioned reports suggested that TLR4 gene might be a contributor to AS.…”
Section: Ta B L E 3 Associations Of Tlr-4 and Tlr-9 Gene Polymorphismmentioning
confidence: 88%
“…IgM with a large molecular weight cannot pass through blood vessel walls, and can be used for early diagnosis of body infections (Macpherson et al, 2008;Liu and May 2016;Hansen et al, 2019;Zhou et al, 2019). TLR4 is a member of the Toll-like receptor superfamily that plays a biological role in the form of binding to ligands (Zhang J. et al, 2019). Tumor cells can release a large number of cytokines in the process of immune remodeling, such as IL-10 and TGF-β, the latter can weaken the killing activity of cytotoxic T lymphocytes and natural killer cells, evading immune surveillance and promote tumor metastasis (Solinas et al, 2010;Wei et al, 2010;Bellomo et al, 2016;Anguiano-Hernandez et al, 2019;Dong et al, 2019).…”
Section: Discussionmentioning
confidence: 99%